ANÁLISE DO FUNCIONAMENTO E DAS AÇÕES DA CAPITANIA FLUVIAL DO PANTANAL/MARINHA DO BRASIL NA ÁREA DE FRONTEIRA ENTRE CORUMBÁ-MS E PUERTO QUIJARRO (BOLÍVIA) - Laurenice da Silva Ferreira (2023)
Corumbá, Ladário and Puerto Quijarro cities are part of what we called border zone and have a red warning light leading to national awareness. It is a vital region with great economic strategy due to its accessibility and commercial exploitation. Also, this area is bordered by four of all South America countries. It is populated, in fact, which makes transnational illegal activities increase. In this sense, the Brazilian Armed Forces' interference is of paramount importance to make sure our country is properly safe. In this way, the purpose of this work is to analise the Pantanal Fluvial Captaincy's inspection development, and their control over the border zone between Corumbá, Ladário and Puerto Quijarro (Bolivia). And the specific point was to give thought on the historical process of Maritime transport through the borders of Brazil/Bolivia, the Pantanal Fluvial Captaincy infrastructure (CFPN), identify routines, activities and actions that were done by CFPN and suggest actions that best fits to this institution and others from the same area. The methodology of this academic work consists of accurate sources, starting at bibliographic content, borders' literature, published articles, websites and similar things. Some unstructured interviews were reported, jointly with the armed forces from Fluvial Captaincy, research articles, books, publications and documents from the internet that somehow introduce relevant contributions on transport, safety and Fluvial investigation at Brazil - Bolivia border.